The Effect of Academic Support, Computer Capability and Government Policy on Student Technopreneur Interest - Dody Setyadi; Irin Mirrah Luthfia; Karnowahadi, Karnowahadi; Luqman Khakim (International Journal of Education, Vocational and Social Science, 2023)
This research examines the influence of student interest in becoming a technopreneur. This study uses three variables namely academic support, computer capability, and government policy as the determining factor. This research is quantitative research with a data collection approach through a questionnaire with a sample size of 120 student respondents at Semarang State Polytechnic. By using multiple linear regression analysis tools with the resulting regression equation Y = 0.080 + 0.597 X1 + 0.450 X2 + 0.190 X3. With the t-test results show that partially academic support and computer capability affect student technopreneur interest. However, the government policy variable has no partial effect on student technopreneur interest. The results of the F test obtained Sig value = 0.000 which shows simultaneously the variables of academic support, computer capability, and government policy have a significant effect on student technopreneur interest.